Acute kidney injury: a common prognostic condition for different pathogenetic triggers? - Cardinale, Daniela; Cosentino, Nicola; Marenzi, Giancarlo (Journal of Thoracic Disease, 2019)
We read with great interest the editorials by Wang et al. (1) and Cagini et al. (2) on our recently published study focusing on acute kidney injury (AKI) after lung cancer surgery (3). We particularly appreciated the editorial consideration reserved for a topic, such as AKI, which is only apparently of relevance for nephrologists.